Impact of static load on voltage stability of an unbalanced distribution system - Gunalan S.; Ramasamy A.K.; Verayiah R. (2023)
Static load which is known for three different characteristics i.e. constant power, constant current and constant impedance shows a different voltage profile because both of their real power and reactive power vary differently as the voltage varies except for constant power. This paper will analyze the impact of each load characteristic individually and also as combination on voltage stability of an IEEE 34 Bus Distribution System by increasing the load demand, and also transient analysis i.e. creating a single phase-to-ground fault i.e. on phase a and balanced three phase fault. The most suitable load to study the voltage stability is also proposed. It was found that, with constant power loads, the reactive power demand increases significantly when load real power and reactive power increases by 25%. Constant current loads and combination loads, on the other hand, the reactive power demand increases but only slightly and the demand is even lesser when with constant impedance loads. However, as the load real power and reactive power increases by 50%, constant power loads causes voltage collapse whilst constant current loads and combination loads turn out to be the next in the order followed by constant impedance loads. In transient analysis, during the single phase fault, with combination loads, phase b voltage increases drastically but only small increment observed in phase c voltage. During the three phase fault, phase b voltage is slightly higher than phase c voltage followed by phase a voltage. As comparison to combination loads, constant power loads causes lesser three phase voltages. After the fault was cleared, a smooth voltage waveform obtained in the period of retaining back to the same pre-fault voltage, however, distortions in the voltage recovering waveform seen when dynamic load included in the system. Constant power load is found to be the suitable load to study the voltage stability. 2010 IEEE.